Pengawasan Otoritas Jasa Keuangan terhadap Praktik Manipulasi Pasar di Pasar Modal Indonesia - Emiel Salim Siregar; Eki Azwani Panjaitan; Nurul Fadilah Hasan; Dita Sasika Rani; Lady Anastasya Putri Sani; Maidani Intan Afiqah Lubis (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Market manipulation practices in the Indonesian capital market have the potential to harm investors, distort fair price formation, and undermine market integrity. These conditions require effective supervision by the Financial Services Authority (Otoritas Jasa Keuangan—OJK) as the institution authorized to regulate and supervise capital market activities. This study aims to analyze the legal framework governing OJK's supervision of market manipulation practices, assess the effectiveness of its implementation, and identify the factors influencing the success of such supervision. This study employed a normative legal research method using statutory and conceptual approaches. Legal materials were collected through library research and analyzed qualitatively. The findings indicate that OJK's supervisory authority is supported by a strong legal framework under Law Number 8 of 1995 concerning the Capital Market and Law Number 21 of 2011 concerning the Financial Services Authority. Nevertheless, the effectiveness of supervision continues to face challenges arising from technological developments, the increasing complexity of market manipulation schemes, and limitations in supervisory capacity. This study concludes that strengthening institutional capacity, optimizing the use of technology, and enhancing inter-agency coordination are essential to improving investor protection and maintaining the integrity of the capital market. The novelty of this study lies in its integrated analysis of the legal framework, supervisory effectiveness, and technology-based market manipulation challenges within a single analytical framework.